BIOTIC CHANGES IN A EUSTATIC CYCLOTHEM: DOMODEDOVO FORMATION (MOSCOVIAN, CARBONIFEROUS) OF PESKI QUARRIES, MOSCOW REGION - Kabanov P.B.; Baranova D.V.; Gorjunova R.V.; Lazarev S.S.; Alekseev A.S.; Malkov V.G. (My University, 2006)
Stacking lithofacies in the Domodedovo Formation of Peski quarries show prominent changes in paleodepth and depositional environment. Distribution in the section of fusulinoids, algae, conodonts, and macrofossils are revealed. Among the latter, brachiopods and bryozoans are discussed in most detail.
Keywords: Moscovian; Paleozoic::Carboniferous::Pennsylvanian::Middle::Moscovian; Палеозой::Каменноугольная::Средний::Московский